Experiência de visitantes com deficiência visual na sala de física do museu de ciências da Universidade Estadual de Maringá - Grandi, Samira Cassote (2017)
In recent years there has been a growing increase in the number of research on Museums and Science Centers around the world. Such environments have been seen as educational spaces that may contribute to the improvement of the quality of the teaching and learning of science. At the same time, the demand for these spaces has become increasingly greater among different audiences. Consequently, there is the issue of social inclusion in the museum environment, which goes beyond physical accessibility, involving concerns in view of the best museum experience for all audiences. In this sense, museum experience is defined as the set composed by the main emotions, sensations, experiences and learning, resulting from the interaction of the visitor with the objects and the speeches inside the museum. In this context, through a case study of a visit made by visually impaired people in the Physics Environment of the Interdisciplinary Dynamics Museum of the State University of Maringá, we aimed to investigate what kind of experience these environments may provide for this specific type of audience. During the visit, together with the non-participant observation, we used the semi-structured interviews to collect pre and post visit data. To help us with the analysis of the data obtained during the visit, we used a set of categories developed by Allen (2002 apud SAPIRAS, 2007). The analysis of the semi-structured interviews data was made following the methodology of the Discursive Textual Analysis by Moraes and Galiazzi (2003). The results showed that the simple care of combining the explanations of the apparatuses with the touch and handling of them was responsible for allowing a gratifying museum experience for the visually impaired visitors. By feeling welcomed by the differentiated attention given in the descriptions of the experiments, the participants became more comfortable and active in the dialogues that occurred during the visit, arousing their interest in learning what was presented in each experiment.